Central African Republic in crisis: African Union Mission needs United Nations support - Annette Weber; Markus Kaim (Stiftung Wissenschaft und Politik (SWP), 2014)
On 20 January 2014 the foreign ministers of the EU member-states approved EUFOR RCA Bangui. The six-month mission with about 800 troops is to be deployed as quickly as possible to the Central African Republic. In recent months CAR has witnessed growing inter-religious violence, the displacement of hundreds of thousands of civilians and an ensuing humanitarian disaster. France sent a rapid response force and the African Union expanded its existing mission to 5,400 men. Since the election of the President Catherine Samba-Panza matters appear to be making a tentative turn for the better. But it will be a long time before it becomes apparent whether the decisions of recent weeks have put CAR on the road to solving its elementary structural problems. First of all, tangible successes are required in order to contain the escalating violence. That will require a further increase in AU forces and the deployment of a robust UN mission. (SWP Comments)
Keywords: 320